Post Endodontic Restoration – Managing challenges for compromised tooth structure with endocrown - Shrestha, Swechhya; Maskey, Brijesh; Mathema, Suraj Ram Bhakta (Journal of Nepalese Prosthodontic Society, 2025)
Restoring endodontically treated teeth with severe coronal loss and limited interocclusal space is challenging. This case presents a mandibular second molar with extensive destruction, short clinical crown, and opposing supraeruption, managed with a lithium disilicate endocrown. After extraction of the adjacent impacted third molar, enameloplasty, and gingival recontouring, the tooth was conservatively prepared and restored with a digitally fabricated endocrown adhesively luted with resin cement. The restoration showed satisfactory fit, esthetics, and function, supporting endocrowns as a conservative and predictable option for compromised posterior teeth.